João Soares Lisboa’s state conceptions: conceptual diversity in the liberal-radical array in a constitutional year - Leme, Marisa Saenz [UNESP] (Coimbra Univ Press, 2022)
This article discusses the proposals for the organization of the state made by the Portuguese trader Joao Soares Lisboa, one of the exponents of the field considered radical-liberal, shaped in the Independence process and the beginning of the First Reign in Brazil. They were presented in his newspaper, Correio do Rio de Janeiro, especially in the 1823 editions, when the Brazilian Constituent Assembly met, a forum in which were confronted different conceptions about the State to be constituted in the country that was then being formed. In a linguistic context of synonymy between the terms federation and confederation, Lisboa distinguished himself by the uniqueness of his conceptions in the face of the political field to which he belonged. These are important differences to be recovered in order to deepen the understanding of the liberal conceptions in Brazil at that time. The formulations presented in the Federalist Articles regarding the themes addressed constituted the theoretical references for evaluation of these conceptions.
Keywords: Liberalism; State; Confederative; Legislative; United